Training on Creating Song Content with the Theme of Religious Moderation for Middle School Students in Jayapura Regency - Sulistyowati, Ambar; Mulder, Deysi O.; Parinussa, Nelinio P.M.; Manupapami, Maria E. (Abdi Masyarakat, 2024)
Training to create song content on the theme of religious moderation for junior high school students in Jayapura Regency aims to instill the values of religious moderation and equip the younger generation with social responsibility in maintaining harmony. By using demonstration and question and answer methods, this training not only facilitates understanding of religious moderation but also involves students in the creative process of song creation. The results of the training show that music has effective emotional power in building solidarity and instilling awareness of the importance of interfaith dialogue and respect for differences. Students not only learn to compose songs, but also develop collaboration and message delivery skills through digital media, making them content producers capable of disseminating messages of religious moderation to a wider community. In conclusion, this training proves that a creative approach to music is an effective way to educate and involve students in spreading the values of religious moderation. By including local and technological elements, this training makes the moderation message more relevant and relatable. This plays an important role in forming a generation that is not only academically intelligent but also has a strong character in respecting diversity, ready to face social and religious challenges in the future.